Evaluar y comparar conocimientos, actitudes y prácticas en hábitos de higiene oral en jóvenes adultos, antes y durante la pandemia por COVID-19 (2021)
To evaluate the CAP of oral hygiene habits in young soldiers who provide the service in the seventh brigade- military district no.5, Villavicencio / Meta before and during the COVID-19 pandemic. Establish the CAP of oral hygiene habits in young adult students of dentistry of the Antonio Nariño university, Villavicencio / Meta headquarters before and during the COVID-19 pandemic.